2022
DOI: 10.1111/dom.14781
|View full text |Cite
|
Sign up to set email alerts
|

Dual‐hormone artificial pancreas for glucose control in type 1 diabetes: A meta‐analysis

Abstract: Aim: To evaluate the efficacy and safety of a dual-hormone artificial pancreas (DH) in type 1 diabetes.Material and Methods: PubMed, Embase, the Cochrane Library and ClinicalTrials.gov were searched for studies published up to February 16, 2022. We included randomized controlled trials that compared DH with single-hormone artificial pancreas (SH), continuous subcutaneous insulin infusion (CSII) or sensor-augmented pumps (SAP), and predictive low glucose suspend systems (PLGS) in type 1 diabetes. The primary ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…A previous meta‐analysis showed that artificial pancreas systems significantly improved glycaemic control among patients with T1DM, and DH‐APSs outperformed SH‐APSs 11 . In contrast, our meta‐analysis focused on exercise‐related glycaemic control.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…A previous meta‐analysis showed that artificial pancreas systems significantly improved glycaemic control among patients with T1DM, and DH‐APSs outperformed SH‐APSs 11 . In contrast, our meta‐analysis focused on exercise‐related glycaemic control.…”
Section: Discussionmentioning
confidence: 88%
“…A previous meta-analysis showed that artificial pancreas systems significantly improved glycaemic control among patients with T1DM, and DH-APSs outperformed SH-APSs. 11 In contrast, our metaanalysis focused on exercise-related glycaemic control. LOPEH can even occur up to 24 h after exercise but has not been attributed adequate importance, leading to 'death in bed' syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…This is especially pertinent in diabetes care, where the development of e.g. novel pharmacological agents (such as GLP-1 (glucose-like peptide 1) receptor agonists1 2 and sodium-glucose cotransporter-2 (SGLT2) inhibitors1 2) and technological innovations (such as flash glucose monitoring,3–6 smart insulin pens6 7 and pumps6 and the artificial pancreas8 9) are rapidly changing the field. To form sensible plans of care that respond well to and advance the situation of the individual patient, that is, to make care fit, patients and clinicians must collaborate to determine what to do, work often referred to as shared decision-making (SDM) 10–13.…”
Section: Introductionmentioning
confidence: 99%
“…These systems use insulin only and still require carbohydrate counting for administering mealtime insulin boluses. In contrast, the newly developed dual hormone fully closed loops (DHFCLs) provide a balanced infusion of not only insulin but also glucagon mimicking physiological conditions 4–7. The user does not have to provide any meal or correction boluses as the DHFCL reactively adapts the insulin and glucagon infusion 5.…”
Section: Introductionmentioning
confidence: 99%